الالتزام التنظيمي وعلاقته بالأبداع الإداري: دراسة ميدانية على مصرف شمال أفريقيا صرمان - نعيمة عبدالسلام الهادي; المهدي علي الهوش (Surman Journal of Science and Technology, 2025)
These studies aimed to determine the relationship between organizational commitment and administrative creativity at the North African Sorman Bank, and to contribute to raising the level of administrative creativity at the bank. objectives of the study, a questionnaire was designed to study in the field the variables of the study problem, in order to test the hypotheses. The study population consisted of all employees of the North African Sorman Bank. The study sample was selected using a comprehensive survey method, where 45 questionnaires were distributed, of which 37 questionnaires were returned, i.e. 82.2%.with a set of results, the most important of which are: 1- The level of belonging and loyalty among the bank’s employees was high .2- Regression analyzes show the existence of a moderate and satisfactory correlation between overall organizational commitment and administrative creativity, which indicates a positive effect of organizational commitment on creativity in the bank .3- The moral loyalty of employees is the most important factor in enhancing administrative creativity in the bank .The study presented some recommendations, the most important of which are:1- Working to organize social activities and honors within the institution to deepen the emotional connection and increase morale .2- The work environment should be improved, development opportunities should be provided, and employees should be motivated to enhance their desire to remain based on their conviction and not for fear of losing alternatives . 3- It is necessary to spread a culture of loyalty and ethical commitment and promote clear institutional values ​​that enhance a positive work environment.